Pengaplikasian Ornamentasi Sape ke dalam Komposisi Baru 'Inscape' Berentak Bossa Nova - Chen,, Hui Meng (Universiti Malaysia Sarawak (UNIMAS), 2018)
Sape is a traditional musical instrument played by the orang Ulu community in Sarawak. The uniqueness of this instrument is the tone color and the ornamentation. The ornamentation of sape is formed through the playing technique of sape. Till now, there are limited records on sape playing techniques. In addition, jazz playing style on sape are increasingly popular. Most of the sape repertoire today are played in contemporary style such as jazz fusion. Other genre of jazz such as swing, cha-cha, or bossa nova are yet to be explored by sape. Therefore, this experimental research hope to combine both ornamentation of sape and bossa nova to produce a new composition.